2022
DOI: 10.3390/su142315884
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Social and Psychological Factors Influencing the Use of Genetically Modified Foods—A Review

Abstract: Due to rapid globalization in the world, the understanding of cultural differences, such as beliefs, values, ways of thinking, and perceptions about new technologies in food processing have also increased. Since the 1990s, when genetically modified (GM) foods were introduced into the food supply, they have provoked many debates. In this review, it was identified and discussed how social and psychological factors influence public attitudes to GM foods and the perceptions of consumers in using GM foods. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The issue of the unnaturalness of GM food and GMOs has been discussed from different angles such as ethics, nutrition, religion, fear, and safety among other less prominent viewpoints. They all refer to the transgenic nature of GM food and GMOs and conclude that the average consumer cannot relate to an end product that contains traits of two or more organisms that are not naturally (or sexually) compatible; therefore, the term "unnatural" and "artificial" appears in different studies and consultations, without any linkages to the scope of the inquiry of the studies, as reported by Siddiqui et al [135].…”
Section: Gmos Ethics and Neophobiamentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the unnaturalness of GM food and GMOs has been discussed from different angles such as ethics, nutrition, religion, fear, and safety among other less prominent viewpoints. They all refer to the transgenic nature of GM food and GMOs and conclude that the average consumer cannot relate to an end product that contains traits of two or more organisms that are not naturally (or sexually) compatible; therefore, the term "unnatural" and "artificial" appears in different studies and consultations, without any linkages to the scope of the inquiry of the studies, as reported by Siddiqui et al [135].…”
Section: Gmos Ethics and Neophobiamentioning
confidence: 99%
“…Regarding fear, i.e., an emotion that is often expressed in food-related issues, consumer attitudes are shaped by the role of neo-phobia [128][129][130][131][132][133][134][135]. In the case of GMOs, foodrelated fears affect the behavior of the consumer.…”
Section: Gmos Ethics and Neophobiamentioning
confidence: 99%
“…The issue of unnaturalness on GM food and GMOs has been discussed from different angles such as ethics, nutrition, religion, fear, safety among other less prominent viewpoints. They all refer to the transgenic nature of GM food and GMOs and conclude that the average consumer cannot relate to an end product that contains traits of two or more organisms that are not naturally (or sexually) compatible, and therefore the term "unnatural" and "artificial" appears in different studies and consultations, without any linkages on the scope of the inquiry of the studies as reported by Siddiqui et al [132].…”
Section: Gmos Ethics and Neophobiamentioning
confidence: 99%
“…Regarding fear, i.e. an emotion that is often expressed in food related issues, consumer attitudes are shaped by the role of neo-phobia [125][126][127][128][129][130][131][132]. In the case of GMOs, food related fears affect the behaviour of the consumer.…”
Section: Gmos Ethics and Neophobiamentioning
confidence: 99%